The Blackwell companion to contemporary Islamic thought - Abu-Rabiʻ, Ibrahim M. (Blackwell companions to religion., 2006)
The Blackwell Companion to Contemporary Islamic Thought reflects the variety of trends, voices, and opinions in the contemporary Muslim intellectual scene. Challenges Western misconceptions about the modern Muslim world in general and the Arab world in particular. Consists of 36 important essays written by contemporary Muslim thinkers and scholars. Covers issues such as Islamic tradition, modernity, globalization, feminism, the West, the USA, reform, and secularism. Helps readers to situate Islamic intellectual history in the context of Western intellectual trends.